The Relationship between Dietary Habits and Type 2 Diabetes for Contribution to Health Promotion: Literature Review - Yolanda Safitri; Tri Krianto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic condition largely influenced by dietary habits and eating behaviors. Poor dietary choices, such as high consumption of refined sugars, unhealthy fats, and low intake of fiber, are well-established risk factors for the development of T2DM. The promotion of healthy eating behaviours and active lifestyles is essential to address the increasing prevalence of T2DM and improve public health. Objective: This study aimed to examine the impact of various dietary patterns and specific food intakes on the risk of T2DM, as well as the role of meal timing and dietary quality in influencing blood glucose levels and insulin sensitivity. Method: This research employs a literature review method by analyzing several relevant studies. The articles were sourced from Scopus and Google Scholar, using keywords such as